OPTIMALISASI BIAYA TRANSPORTASI PENDISTRIBUSIAN KERAMIK MENGGUNAKAN MODEL TRANSPORTASI METODE STEPPING STONE (STUDI KASUS: PT. INDAH BANGUNAN) - Pranati, N M A; Jaya, A I; Sahari, A (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
PT. Indah Bangunan is a distributor of ceramics in the city of Palu. This study aims are to obtain the cost of an optimal transportation in ceramic distribution. To obtain the objectives of this research several steps are done, namely: by creating a model of the transportation of the data obtained, by determining the initial solution using the method of Vogel’s Aprproxumation, and by optimizing the solution using the of Stepping Stone.From the researchits are found that theinitial solution is .  and the optimal solution is  , while the cost of transportation from the company beforeoptimization is .000.It means that PT. Indah Bangunan Palu can optimize the costs of transport for the distribution of ceramics on September 2016 with a cost savings of  or .